An Appraisal of Sea Robbery Control in Nigeria’s Waterways: Lessons from Niger Delta Region - Adongoi, Toakodi; Otodo, Ifeanyichukwu; Azibasuam, Adioni-Arogo (International Journal of Criminology and Sociology, 2019)
This study examined strategies adopted by relevant security agencies to curb sea robbery in Niger Delta Region of Nigeria. A multi-stage sampling technique was employed to select respondents’. A Sample of 400 was derived using Taro Yamane sample size determination technique. Questionnaires and oral interview were the methods used for data collection, while data collected were analysed using descriptive statistics. Results revealed that the joint task force (JTF) is selective in carrying out its constitutional mandate as their presence is felt only in critical facilities, which implies that security is porous and much is needed to guarantee safety of lives and properties on Nigeria territorial waters. Consequent upon this finding, crime-mapping as indicated on GIS map of sample states is recommended.